Nuevos retos de la Documentación en los medios de comunicación - García Jiménez, Antonio (2015)
This special issue, presented by index.comunicación, is focused on media related information & documentation. This field undergoes constant and profound changes, especially visible in documentation processes. A situation characterized by the existence of tablets, smartphones, applications, and by the almost achieved digitization of traditional documents, in addition to the crisis of the press business model, that involves mutations in the journalists’ tasks and in the relationship between them and Documentation. Papers included in this special issue focus on some of the concerns in this domain: the progressive autonomy of the journalist in access to information sources, the role of press offices as documentation sources, the search of information on the web, the situation of media blogs, the viability of elements of information architecture in smart TV and the development of social TV and its connection to Documentation.